Optimal exposure targets for vancomycin in the treatment of neonatal coagulase-negative Staphylococcus infection: A retrospective study based on electronic medical records - Quanyao Chen; Jun Wan; Wei Shen; Wanlong Lin; Xiuxian Lin; Zhiyi Huang; Min Lin; Yao Chen (Elsevier, 2022)
Background: The currently advocated ratio of area under the curve (AUC) over 24 h to minimum inhibitory concentration (AUC/MIC) > 400 and AUC < 600 mg h/L as the therapeutic drug monitoring (TDM) target of vancomycin is based on data from multiple observational studies in adult patients with methicillin-resistant Staphylococcus aureus (MRSA) infection. It may not be applicable to newborns with coagulase-negative Staphylococcus (CoNS) infection. We conducted a retrospective study to identify the optimal exposure targets for vancomycin in the treatment of neonatal CoNS infection. Methods: Based on the inclusion and exclusion criteria, serum vancomycin concentration, demographics, clinical data, and related laboratory data of newborns who received vancomycin intravenous infusion from June 1, 2016 to February 1, 2021 were collected retrospectively. The AUC was calculated using the maximum a posteriori Bayesian (MAPB) method. The vancomycin exposure threshold of AUC/MIC for efficacy and AUC for toxicity (acute kidney injury, AKI) were determined based on receiver operating characteristic (ROC) curve analysis. The correlation between vancomycin exposure and both clinical effect and nephrotoxicity was analyzed using logistic multivariate regression. Results: In total, 153 patients and 245 vancomycin concentrations (160 trough and 85 peak concentrations) were included. The ROC curve analysis showed that the exposure thresholds of AUC/MIC for clinical efficacy and AUC for nephrotoxicity were 281 and 602 mg h/L, respectively. The multivariate regression analysis showed that AUC/MIC > 280 was a predictor of efficacy (OR: 13.960, 95% CI: 1.891-103.078, P < 0.05) and AUC > 600 mg h/L was associated with AKI (OR: 9.008, 95% CI: 2.706-29.983, P < 0.05). The vancomycin AUC/MIC threshold for treating neonatal CoNS infection with vancomycin is lower than the currently advocated AUC/MIC >400. Conclusion: The optimal exposure targets for vancomycin in neonatal CoNS infection were AUC/MIC > 280 and AUC < 600 mg h/L.